Pre-service and first-year teachers' transactions with mathematics pedagogy textbooks - Brass, Amy (2018)
Despite the ubiquitous use of pedagogy textbooks within teacher education programs, research examining the relationships between pre-service teachers and their pedagogy textbooks is scarce. This study draws on Rosenblatt's (1982) transactional theory of reading to explore how pre-service teachers and first-year teachers transact with mathematics pedagogy textbooks. We interviewed sixteen participants – seven pre-service teachers and nine first-year teachers – about their transactions with mathematics pedagogy textbooks, how instructors encouraged participants' transactions with these textbooks, and the messages participants received from the textbooks. Results suggest that supporting pre-service teachers with textbook use is crucial for them to make connections between textbooks and the broader educational landscape. The results also uncovered tensions between participants' perceptions of textbook information and their own classroom experiences. We suggest future research to explore approaches that foster transactions to help pre-service teachers negotiate and question textbooks in stronger ways